2022
DOI: 10.4049/immunohorizons.2200029
|View full text |Cite
|
Sign up to set email alerts
|

Level and Duration of IgG and Neutralizing Antibodies to SARS-CoV-2 in Children with Symptomatic or Asymptomatic SARS-CoV-2 Infection

Abstract: There are conflicting data about level and duration of Abs to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in children after symptomatic or asymptomatic infection. In this human population, we enrolled adults and children in a prospective 6-mo study in the following categories: 1) symptomatic, SARS-CoV-2 PCR + (SP + ; children, n 5 8; adults, n 5 16), 2) symptomatic, PCR À , or untested (children, n 5 27), 3) asymptomatic exposed (children, n 5 13), and 4) asymptomatic, no known exposure (child… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Almost half of the children in the asymptomatic group tested negative. Previous studies have suggested that humoral immunity persists longer based on symptoms derived from the infection 9,13 . However, this fact has not yet been confirmed in children and cannot be derived from our results, even though they are along these lines.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Almost half of the children in the asymptomatic group tested negative. Previous studies have suggested that humoral immunity persists longer based on symptoms derived from the infection 9,13 . However, this fact has not yet been confirmed in children and cannot be derived from our results, even though they are along these lines.…”
Section: Discussioncontrasting
confidence: 76%
“…It is already known that there is a gradual decrease in antibodies after primary infection in adults. 9,10 Previous studies reported remarkable persistence in the paediatric population. 1 In our study, we observed that all patients tested <1 year after acute infection were still positive for antispike IgG, and no patient tested negative for serology before day 411 after the infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Khaitan et al,. as part of the DISCOVER study ( 34 ), measured neutralizing Abs (nAbs) and IgG Abs to SARS-CoV-2 Ags and spike protein variants in symptomatic and asymptomatic children. They found that children developed nAbs that remained detectable longer than in adults but waned in titer over time and broad IgG Abs that also waned in level over time.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, individuals that were in the COVID-19 positive asymptomatic pediatric controls group came to the hospital for some reason other than SARS-CoV-2 and were enrolled in this study because they were incidentally found to be SARS-CoV-2 positive by nuclei acid testing. (Khaitan et al, 2022). We also utilized sequencing data from 20 additional MIS-C samples collected at the Karolinska Institute.…”
Section: Human Subjectsmentioning
confidence: 99%